Oral bisphosphonate use and age-related macular degeneration: retrospective cohort and nested case-control study - Garriga, C; Pazianas, M; Hawley, S; Delmestri, A; Prieto-Alhambra, D; Cooper, C; Judge, A (Wiley, 2018)
Background Hydroxyapatite (calcium and phosphate) spherules have been implicated in the initiation and establishment of age-related macular degeneration. Bisphosphonates could increase the dissolution of hydroxyapatite crystals and when they are used in elderly patients with osteoporosis they could reduce the risk of developing age-related macular degeneration. Objective To determine if oral bisphosphonate (BP) use is associated with the incidence of age-related macular degeneration in a large “real-world” population-based cohort of incident hip fracture patients. Design A cohort of 13,974 hip fracture patients (1999 to 2013) were used to conduct a: (a) propensity score matched cohort analysis and (b) nested case-control analysis. Setting A population-based study using electronic health records from UK primary care (Clinical Practice Research Datalink). Participants Hip fracture patients aged ≥50 years without age-related macular degeneration diagnosis prior to hip fracture date or in the first year of follow-up. Prior BP-users and those who died, transferred out or with last data collected before hip fracture were excluded. Exposures Incident BP use following hip fracture. BP use was further categorised according to medication possession ratio in quartiles. Main outcome measures Primary outcome was a diagnosis of age-related macular degeneration after the first year from index date. Propensity scores were used to match 1:1 BP-users to non-BP users. Covariates in the propensity score were index year, age, gender, body mass index, smoking, alcohol drinking, region, drug confounders and comorbidities. Subhazard ratios and their 95% confidence intervals were calculated including death as a competing risk. A nested 1:20 case-control analysis using conditional logistic regression provided risk estimates according to medication possession ratio. Results Among 6,208 matched patients and during 22,142 person-years of follow-up, 57 (1.8%) and 42 (1.4%) age-related macular degeneration cases occurred in BP-users and non-BP users, respectively. The survival analysis model did not provide significant evidence of a higher risk of AMD in BP-users (subhazard ratio: 1.60; CI: 0.95-2.72; P=0.08) although there was a significant increased risk among BP-users with high medication possession ratio (top quartile) relative to non-BP users (odds ratio: 5.08, 3.11-8.30; P <0.001, respectively). Conclusions Overall, oral BP use was not associated with an increased risk of age-related macular degeneration in this cohort of hip fracture patients, although the risk increased significantly with higher medication possession ratio. More data are needed to confirm these findings.